The Study of Starch Seeds Durian (Durio zibethinus) Effect as the Filler Material on Tensile Strength and Biodegradation of Polymers Polystyrene (PS) - Rifka Sudi; Irhamni .; Rahmi . (Journal of Aceh Physics Society, 2013)
The study of starch seeds durian (Durio zibethinus) effect as the filler material on tensile strength and biodegradation of polymers polystyrene (PS)  has been done. In this study, the sample was made with 5 variations of Polystyrene:Starch:glycerol as follows:(95:0:5; 90:5:5; 85:10:5; 80:15:5 and 75:20:5) %. The samples were made using the hotpress machine and the ASTM D368 standard. The mechanical properties (tensile strength) were tested using a tensile tester. The testing for functional groups were using FT-IR. The surface morphology was obtained by AFM and biodegradation through burial the samples for 40 days (time of observation 1, 2, 3, 4 and 5 weeks). As the results showed that the tensile strength values are influenced by variations in the composition of composite materials. The optimum tensile strength values were obtained on samples of PS-2 (90% of PS: 5% of Starch: 5% of glycerol) with a tensile strength value of 0.55 kgf / mm². Based on the analysis of functional groups, it was found that there is no chemical reaction, which is characterized by the emergence of new functional groups on the composite sample. The surface morphology observation showed that the variation does not affect the relative composition of the surface morphology of the samples. Biodegradation test results showed that the samples of PS-4 and PS-5 began degraded after burial for 4 weeks.